PERANCANGAN APLIKASI HASHING FILE MENGGUNAKAN SHA – 224 BERBASIS ANDROID - Pasaribu, Hendra; Harahap, Muhammad Fauzi (Jurnal Mantik Penusa, 2020)
Nowadays the development of technology in the field of computer science is growing rapidly. With the rapid development of technology in the field of computer science, information and data require a security and confidentiality because the information becomes a very valuable item. However, with the development of technology there are also many threats of crime against files that users have. One way to maintain the authenticity of information and data is to use hash cryptography. The hash function is an algorithm that converts text / messages into a series of random characters that have the same number of characters. The hash function is used to guarantee the authentication service of messages or files. Algorithms that use hash functions include MD5, SHA-1, SHA-2 (SHA - 224, SHA - 256, SHA - 384, SHA - 512) and others that have their advantages and disadvantages. In designing this application, the cryptographic algorithm used is the SHA-224 algorithm, because SHA-224 has a summary of variable sizes. The file hashing application using the Android-based SHA-224 algorithm, can help users to maintain the authenticity of files from users anywhere and anytime. Users can also compare the authenticity of user files with files that have been hashed.Keywords: hash function, one-way hash, SHA-224, file hash, Android